2018
DOI: 10.20491/isarder.2018.400
|View full text |Cite
|
Sign up to set email alerts
|

How Does Customer Experience Shape the Attitude Towards and Intention to Brand Switching

Abstract: Customer Experience (CeX) and Brand Switching Behavior (BsB) of customers play an important role in the market performance of brands. The underlying relationship between these two constructs to shed light into the success factors in the contemporary consumer markets. This study aimed to (1) explore the relationship between CeX and BsB behavior including Attitude Toward Switch (AtS) and Intention to Switch (ItS), (2) understand the effects of CeX on Customer Satisfaction (CuS), Brand Trust (BaT) and Brand Loyal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 72 publications
(92 reference statements)
0
4
0
Order By: Relevance
“…Delgado-Ballester and Sabiote (2015) also observed that brand experiences positively influence the consumer-based brand equity and a positive mouth-to-mouth, showing that the experiential value of products and services is more important than the functional value. In addition, brand experience has a significant direct and positive effect in brand personality, consumer satisfaction, brand loyalty and in consumer-brand relationship (Başer, Cintamür & Arslan, 2015;Keng et al, 2013;Ramaseshan & Stein, 2014;Sözer & Civelek, 2018). Ong, Salleh and Yusoff (2015) confirm a positive and direct relationship between brand experiences and brand loyalty, highlighting the importance of developing experiences considering the difficulty of replicating the intangible and experiential aspects of brand experiences.…”
Section: Conceptual Modelmentioning
confidence: 84%
“…Delgado-Ballester and Sabiote (2015) also observed that brand experiences positively influence the consumer-based brand equity and a positive mouth-to-mouth, showing that the experiential value of products and services is more important than the functional value. In addition, brand experience has a significant direct and positive effect in brand personality, consumer satisfaction, brand loyalty and in consumer-brand relationship (Başer, Cintamür & Arslan, 2015;Keng et al, 2013;Ramaseshan & Stein, 2014;Sözer & Civelek, 2018). Ong, Salleh and Yusoff (2015) confirm a positive and direct relationship between brand experiences and brand loyalty, highlighting the importance of developing experiences considering the difficulty of replicating the intangible and experiential aspects of brand experiences.…”
Section: Conceptual Modelmentioning
confidence: 84%
“…Meanwhile, according to (Han 2015;Han & Hwang, 2015), switching intention is the desire of a company's customers to use products and services from other companies. In hotels, services and product retail, switching intention usually occurs because of an unpleasant experience when trying products and services (Liang et al, 2018;Sözer & Civelek, 2018). But dissatisfaction is not the only reason.…”
Section: Switching Intentionmentioning
confidence: 99%
“…There are five types of customer experience as the basis for experiential marketing analysis overall, namely: sense, feel, think, act, and relate (Schmitt, 2010). Customer experience influences the switching intention (Liang et al, 2018;Sözer & Civelek, 2018). Customer experience is affected by price (Kamaladevi, 2010;Wang et al, 2018) and service quality (Gracia et al, 2011;Jang & Namkung, 2009;Palmer, 2010).…”
Section: Customer Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…The results of the path analysis test proved that satisfaction, variety seeking, and attractiveness alternatives have indirect effects on switching behavior through switching intentions. The study of Sozer and Civelek (2018) observed how customer experience influences customer satisfaction and switching behavior. The results of the study prove that customer experience is proven to affect attitude toward switching and intention to switch.…”
Section: Introductionmentioning
confidence: 99%